Le menzioni di Aristotele nel Kitāb al-ifāda wa-l-iʿtibār di ʿAbd al-Laṭīf: Appunti preliminari in vista della prima traduzione italiana del Racconto d’Egitto - Bellucci, Nikola D. (Folia Orientalia, 2019)
In view of the first Italian translation of the Kitāb al-ifāda wa-l-iʿtibār by ʿAbd al-Laṭīf, this article intends to provide a brief critical report of the mentions of Aristotle found in the Account of Egypt.